Cortical signature of clock drawing performance in Alzheimer's disease and mild cognitive impairment - Hirjak, Dusan; Wolf, Robert Christian; Kubera, Katharina Maria; Thomann, Anne K.; Maier-Hein, Klaus H.; Schröder, Johannes; Thomann, Philipp (Journal of psychiatric research, 2017)
It is unclear whether clock drawing test (CDT) performance relies on a widely distributed cortical network, or whether this test predominantly taps into parietal cortex function. So far, associations between cortical integrity and CDT impairment in Alzheimer's disease (AD) and mild cognitive impairment (MCI) largely stem from cortical volume analyses. Given that volume is a product of thickness and surface area, investigation of the relationship between CDT and these two cortical measures might contribute to better understanding of this cognitive screening tool for AD. 38 patients with AD, 38 individuals with MCI and 31 healthy controls (HC) underwent CDT assessment and MRI at 3 Tesla. The surface-based analysis via Freesurfer enabled calculation of cortical thickness and surface area. CDT was scored according to the method proposed by Shulman and related to the two distinct cortical measurements. Higher CDT scores across the entire sample were associated with cortical thickness in bilateral temporal gyrus, the right supramarginal gyrus, and the bilateral parietal gyrus, respectively (p < 0.001 CWP corr.). Significant associations between CDT and cortical thickness reduction in the parietal lobe remained significant when analyses were restricted to AD individuals. There was no statistically significant association between CDT scores and surface area (p < 0.001 CWP corr.). In conclusion, CDT performance may be driven by cortical thickness alterations in regions previously identified as “AD vulnerable”, i.e. regions predominantly including temporal and parietal lobes. Our results suggest that cortical features of distinct evolutionary and genetic origin differently contribute to CDT performance.
Gesehen am 17.07.2018